2007
DOI: 10.1152/physiolgenomics.00232.2006
|View full text |Cite
|
Sign up to set email alerts
|

A genetic mouse model to investigate hyperoxic acute lung injury survival

Abstract: Acute lung injury (ALI) is a devastating disease that maintains a high mortality rate, despite decades of research. Hyperoxia, a universal treatment for ALI and other critically ill patients, can itself cause pulmonary damage, which drastically restricts its therapeutic potential. We stipulate that having the ability to use higher levels of supplemental O2 for longer periods would improve recovery rates. Toward this goal, a mouse model was sought to identify genes contributing to hyperoxic ALI (HALI) mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 39 publications
6
30
1
Order By: Relevance
“…Transgressive segregation is not uncommon (18,32,34,36) and is most frequently observed in intraspecific crosses involving inbred populations (34). In a QTL mapping study for hyperoxic acute lung injury, a transgressive allele was similarly uncovered as the second strongest locus for the trait (33). This class of genetic variation might be also viewed as cryptic genetic variation (CGV).…”
Section: Discussionmentioning
confidence: 99%
“…Transgressive segregation is not uncommon (18,32,34,36) and is most frequently observed in intraspecific crosses involving inbred populations (34). In a QTL mapping study for hyperoxic acute lung injury, a transgressive allele was similarly uncovered as the second strongest locus for the trait (33). This class of genetic variation might be also viewed as cryptic genetic variation (CGV).…”
Section: Discussionmentioning
confidence: 99%
“…Ozone, one of the most potent oxidants known (13), quickly produces a pulmonary response in inbred mice that resembles the exudative phase of ARDS; at doses greater than or equal to 4 ppm, ozone causes death within 2 days (14). In contrast to the rapid time course of ozone, nickel (15) and hyperoxia (16,17) can induce ALI mortality within 3 to 4 days in sensitive strains, but resistant strains of mice can survive as long as 10 to 12 days. Importantly, at a time just before their respective mean survival times (MSTs), certain pathologies of ozone-, nickel-, and hyperoxiainduced ALIs are similar in various inbred mouse strains (18,19), suggesting a possible overlap in the injury response to the different oxidants.…”
mentioning
confidence: 99%
“…We selected adult, male mice for this study, because the original investigation that identified Nrf2 as a susceptibility gene for hyperoxiainduced ALI used B6 and C3 mice with this age and gender (7). However, a role of gender in model ALI induced by hyperoxia has been demonstrated as indicated by differential disease susceptibility (29,30,37). We have also found that, although Nrf2 has an important protective role in the neonatal pulmonary response to hyperoxia (11), it was not associated with neonatal susceptibility to hyperoxia as determined in a genome-wide association study with 30 inbred strains of mice (35).…”
Section: Fig 5 Functional Assessment Of Snp Haplotypes In Vivo (A)mentioning
confidence: 74%